Relation of Lean Body Mass and Muscle Performance to Serum Creatinine Concentration in Hemodialysis Patients - Vodičar, Janez (Biomed Res Int, 2018)
INTRODUCTION: Serum creatinine concentration is an important uremic marker and predictor of survival in dialysis patients. This cross-sectional case-control study was made to quantitatively describe the relation between lean body mass (LBM), physical performance measures, and serum creatinine values. METHODS: Ninety hemodialysis patients and 106 controls were measured by bioimpedance spectroscopy, handgrip strength, sit-to-stand test, and biochemical serum tests. Univariate and multivariate general linear models were used to analyze quantitative relations. RESULTS: At univariate regression LBM accounted for 13.6% variability of serum creatinine concentration. In adjusted analyses with age, height, and body mass, LBM persisted as the only significant predictor of midweek predialysis serum creatinine concentration. Physical performance measures handgrip strength and sit-to-stand performance did not improve prediction of serum creatinine. With addition of serum urea concentration and residual diuresis the predictive value of the regression model improved to account for 45% of serum creatinine variability. Each kg of LBM was associated with 7.7 μmol/l increase in creatinine concentration (95% CI 3.4-12.1, p=0.001). CONCLUSION: Bioimpedance derived LBM has a significant linear relation with predialysis serum creatinine concentrations. Hereby described quantitative relation should help clinicians to better evaluate observed creatinine concentrations of hemodialysis patients when bioimpedance derived LBM is available.